2014
DOI: 10.1177/0269216314545006
|View full text |Cite
|
Sign up to set email alerts
|

Promoting palliative care in the community: Production of the primary palliative care toolkit by the European Association of Palliative Care Taskforce in primary palliative care

Abstract: Many barriers and facilitators were identified. The primary palliative care toolkit can help community-based palliative care services to be established nationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 16 publications
0
72
0
8
Order By: Relevance
“…Factors include the place of the PCP in the healthcare system, access to essential medicines, the existence or otherwise of community nurses attached to primary care, and health insurance arrangements. 215 The WHO Public Health Strategy for palliative care describes four domains of public policy to facilitate community-based palliative care (fi gure 7), 216 and primary care involvement in palliative care should be embedded in all of these domains.…”
Section: Primary Care and National Health Modelsmentioning
confidence: 99%
“…Factors include the place of the PCP in the healthcare system, access to essential medicines, the existence or otherwise of community nurses attached to primary care, and health insurance arrangements. 215 The WHO Public Health Strategy for palliative care describes four domains of public policy to facilitate community-based palliative care (fi gure 7), 216 and primary care involvement in palliative care should be embedded in all of these domains.…”
Section: Primary Care and National Health Modelsmentioning
confidence: 99%
“…PC can then be started at any stage of a chronic disease, and in conjunction with curative or lifeprolonging treatments (4) . While some studies have shown that PHC professionals consider PC as part of their responsibilities to their patients, it is still known that few patients with chronic diseases receive adequate and quality PC in this level of care (1,3,5) . An important challenge for implementing PC in PHC is the appropriate assessment of the patient, including identifying the parameters that scientifically and clinically support their diagnosis.…”
mentioning
confidence: 99%
“…There is a lack of literature sources regarding global trends in the development of pediatric palliative care. Unfortunately awareness of the possibility of receiving palliative care for children is low, and the number of online resources of information on pediatric palliative care is extremely limited [2]. Kharkiv region is the largest in area and population of Ukraine (2.95 million people), but there is no access to PPC for children with life-limiting and life-threating diseases [2].…”
Section: о о ріга джоан марстон а ю пеньковmentioning
confidence: 99%